Butoh Translations and the Suffering of Nature. (3rd July 2016) - Fraleigh, Sondra
Abstract : Butoh, a form of dance and theatre having its roots in midtwentieth-century Japan, continues to migrate across cultures through translations that are individually crafted and understood. It has never been a progressive art, sinking as it does toward mud and disappearance. It is not based on steps, but rather on images and atmospheric change, eliciting affects of bodily being. Most significantly for this essay, butoh brought marks of suffering into dance, sublimating the body while extending its liminal, intermediate states. Butoh seldom lands anywhere: it keeps morphing.